The Evolution of the Vitruvian Recipes over 500 Years of Floor‐Making Techniques: The Case Studies of the Domus delle Bestie Ferite and the Domus di Tito Macro (Aquileia, Italy). (26th April 2017) - Secco, M.; Dilaria, S.; Addis, A.; Bonetto, J.; Artioli, G.; Salvadori, M.
Abstract : The paper reports the results of a research project aimed at the characterization of the floor bedding mortars of two Roman houses in Aquileia (north‐eastern Italy), the Domus delle Bestie Ferite and the Domus di Tito Macro. Seventy floor bedding mortars of the two domus were selected and almost half were fully minero‐petrographically characterized by means of optical microscopy operated in transmitted light (OM‐TL), X‐ray powder diffraction analyses coupled with quantitative phase analysis by means of the Rietveld method (XRPD‐QPA) and scanning electron microscopy with EDS microanalysis (SEM–EDS). The results indicate an evolution of the mortar preparation techniques over time in the mosaic of both houses. The materials are compared to the traditional Roman recipes for specific construction techniques.